EU rights and Brexit hub, 2020-2023 - O'Brien, Charlotte (UK Data Service, 2024)
This is an interdisciplinary, inter-institutional, multi-method three-year project investigating how Brexit affects the social rights of EU & EEA nationals in the UK. It is funded by an ESRC Governance After Brexit Grant. This data collection brings together the results of an advice-led ethnographic study and a series of stakeholder interviews. The advice-led ethnography data deposited consists of numbered case files; we have only uploaded the files for cases for which we had permission to archive the data. Each case folder contains an excel spreadsheet collating all communications – redacted transcripts of emails and summaries of phone calls and meetings. Each separate communication is in a different cell. Where advice requests were accompanied with documents, these are described in a document summary pdf, highlighting key arguments and quotes. Where advice given was accompanied with documents that we compiled, these have been redacted and included. The stakeholder interviews are grouped into two zip files, each containing interview transcripts as word documents. The data includes 20 parliamentary transcripts with MPs and Lords, and 9 transcripts of interviews with non-governmental organisations. We wanted to ask: how well are EU nationals’ rights protected? Do they face administrative obstacles or discrimination when accessing public services? How are EU rights asserted (or jeopardised) in post-EU law? What does transition mean for EEA nationals in the UK? How will future uncertainty affect their ability to claim existing rights now? And will they face administrative obstacles, or discrimination when accessing public services? This project seeks to tackle these questions, to avoid the problems posed by transition from being neglected as researchers look beyond transition. In theory, legal rights will remain mostly unchanged during transition. In practice, however, the perception and anticipation of change can create uncertainty and confusion, which affects how easily rights are accessed. The PI's recent research on the EU Rights Project suggested that risks to administrative justice become more acute in periods of legal transition, making this study vital. The period of transition could be administratively intense, with a lot of people attempting to secure rights, through congested decision-making machinery. In the face of time pressure, insufficient capacity, hastily-produced guidance and confusion over the law, there is a risk that EEA nationals will face obstacles to accessing public services, and these factors could disempower those at greatest risk of social exclusion. This project will capture the human dimension of transition, documenting how guidance, confusion and changes in attitudes play out in accessing public services. We will set up the first ever national EEA legal action research clinic, receiving cases from advice organisations working with EEA nationals, in order to document the problems in accessing public services like social security, housing, health and social care, as a result of, e.g. administrative hurdles, erroneous decisions, poor guidance, or changing administrative culture and attitudes. The clinic will, in parallel, offer specialist, second tier advice and drafting support to advisers from around the UK, on the rights and entitlements of EEA nationals during transition. EEA PSRC will push the boundaries of legal research, embedding legal action research within EU legal studies, as a means to uncover obstacles to justice that would otherwise remain invisible. It will draw upon the methodology pioneered by the EU Rights Project - advice-led ethnography, which produces rich, compelling data, and important evidence of law in action. EEAPSRC builds on this - to produce a legal action research clinic in its own right, with a national reach, clinic student teams, and a focus on systemic administrative problems arising from the state of transition, and a study of the effects of uncertainty upon administrative justice. This empirical work bridges a gap between academic legal theory and practical advice work, by bringing together the PI's technical knowledge of both EU law and UK public law, her Citizens Advice case work experience, her clinic directorship experience, and the resources of the YLS clinic team. To get a sense of the potential scale of the problems identified through the clinic and interviews, we will also analyse new data sets as they are released during the course of the project, on public service eligibility and access. Together these elements will form a rich, nation-wide, interdisciplinary analysis of the effects of transition upon EEA nationals' rights, with significant impact potential. In gathering data from around the UK on how transition plays out in EEA nationals' relationships with UK public services, and on institutional practices that impede access to justice for EEA nationals, while offering expertise to nationwide networks of legal advisers, EEA PSRC will be a national hub - and a European leader - for legal action research.